Aplikasi Akademik Berbasis SMS Gateway Pada SMP XYZ - Yosianus Robertus Isak (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2013)
Short Message Service ( SMS ) is a service that widely applied in wireless communication system, allowing for delivery in the form of alphanumeric messages between customer terminals or between terminals customers with external systems such as email , voice mail , and so on . SMS -based service has been used for many years , the penetration of mobile phones and many users are using other services have made SMS-based service into an attractive service . Now the service automation is used to communicate briefly with students or their parents briefly in the school . SMP XYZ is a Junior High School, which is one of the few schools that continue to improve services to students  academically both facilities and policies . Based mobile applications are expected to provide a more comfortable facility for students to undertake learning in school . Up to this time if they want to see the value of the subject matter , students or parents are always required to come to school . It would be far better to make the system more flexible so the they can see the value easily without the hassle of coming to school. SMS application server in SMP XYZ   is expected to help students and parents who can not attend to school because of the limitations of distance and time to be able to see the value of academic students through mobile media . and the schools can provide the information to students without having to visit the school and disseminate information to students in a school environment.